Dimeric Mn(ii), Co(ii), Ni(ii) and Cu(ii) complexes of a common carboxylate-appended (2-pyridyl)alkylamine ligand: structure, magnetism and DFT study. (12th August 2021) - Manda, Munirathnam; Arora, Himanshu; Sengupta, Arunava; Kant, Shashi; Lloret, Francesc; Mukherjee, Rabindranath
Abstract : Weak anti- (1 ) and ferro-magnetic (2–4 ) interactions are observed in [MII2(L 3 )2 (S)2 ] 2+ (Mn 1, Co 2, Ni 3 ) (S = MeOH) and Cu 4 (S = none). Abstract : Four new complexes of composition [MII2(L 3 )2 (CH3 OH)2 ](ClO4 )2 (M = Mn, 1 ; Co, 2 ; Ni, 3 ) and [CuII2(L 3 )2 ](ClO4 )2 (4 ) (L 3 (−) = 3-[2-(((6-methyl)pyridin-2-yl)methyl){(dimethylamino)ethyl}-amino]propionate) have been synthesized and characterized. Structural analysis reveals that 1–4 are discrete syn – anti carboxylate-bridged binuclear coordination complexes with a {MII2(–O–C–O–)2 } 2+ structural motif. In 1–3 distorted octahedral MN3 O3 and in 4 distorted square pyramidal CuN3 O2 coordination is satisfied at each M(ii ) center by three N (a pyridyl and two tertiary aliphatic amines) and a carboxylate O of the ligand, and an O of the carboxylate group. In 1–3 the M(ii ) center is also coordinated by a CH3 OH molecule. Variable-temperature magnetic measurements reveal the presence of weak antiferromagnetic interactions in 1 and weak ferromagnetic interactions in 2–4 . The electronic structure of 1–4 has been probed by density functional theory (DFT) calculations at the B3LYP level of theory. In order to gain insight into the origin of the observed electronic transitions, time-dependent (TD)-DFT calculations have been done.